Roles and responsibilities of nurses in tobacco control and addiction treatment - Kamışlı, Songül (Journal of Dependence, 2025)
Tobacco addiction ranks among the top preventable causes of death; nevertheless, 8 million people worldwide continue to lose their lives each year due to direct or indirect causes related to tobacco use. Combustible tobacco products like cigarettes and non-combustible products like hookah and e-cigarettes contain nicotine, which leads to addiction. Since tobacco addiction is both a physical and psychological dependence, pharmacological and psychosocial interventions are necessary for treatment. Most tobacco users attempt to quit but often fail. Treating tobacco addiction on its own is difficult, and therefore professional help is needed. Nurses, who are key members of the healthcare workforce, are essential health professionals who can assist with tobacco control and the treatment of tobacco addiction. Despite their known heavy workloads and long shifts, the smoking cessation counseling they provide can make significant contributions to the country's healthcare system, economy, and the quality of life in society. Nurses can contribute by providing counseling in addiction treatment, offering psychosocial support to individuals during their tobacco cessation efforts, and monitoring pharmacological treatments. Nurses who have received training in smoking cessation can enhance individuals' motivation to quit smoking, offer strategies to cope with addiction, and provide guidance. Additionally, by participating in tobacco control efforts, nurses can help raise public awareness and support efforts to reduce tobacco addiction. This article reviews the treatment and intervention efforts for tobacco addiction and discusses the counseling role of nurses.
Keywords: Tobacco prevention; smoking cessation; nursing; counselling